Effect of leadership patterns on the phenomenon of jop burnout among employees at Baghdad College of Economic Sciences University - بريسم, ماجد; فنجان, محمد رحمة (Journal of Economics and Administrative Sciences, 2020)
This study deals with the impact of leadership styles in its three main dimensions (democratic, autocratic, lenient) as an independent variable of the dimensions of functional combustion (emotional stress, inhumanity, personal achievement). The research sought to achieve a set of goals, the most prominent of which are: studying the reality of the researched organization to identify the leadership patterns used in its management and its impact on the phenomenon of functional combustion, Moreover, knowing the extent of support for these established patterns and their contribution to mitigating the phenomenon of functional combustion in the organization's environment, and testing the impact of these leadership patterns on the phenomenon of functional combustion. The research adopted an analytical and descriptive approach, and also identified a set of hypotheses that have been tested by the (spss) program. Through extracting the arithmetic mean, its rations, coefficient of variation and standard deviation, and knowing the amount of influence through calculating the calculated F, then a random sample consisting of (50) teaching and administrative staff were chosen from “Baghdad University College for Economic Sciences” out of (150) is the research community. The research reached a set of conclusions, the most important of which is that the total leadership patterns had a reasonable effect on the phenomenon of functional combustion of the researched organization. The research also presented a set of recommendations aimed at reducing the size of the problem studied.